Comparison of PanBio Dengue Duo Enzyme-Linked Immunosorbent Assay (ELISA) and MRL Dengue Fever Virus Immunoglobulin M Capture ELISA for Diagnosis of Dengue Virus Infections in Southeast Asia - Cuzzubbo, Andrea J. (American Society for Microbiology, 1999)
The performances of the MRL dengue fever virus immunoglobulin M (IgM) capture enzyme-linked immunosorbent assay (ELISA) and the PanBio Dengue Duo IgM capture and IgG capture ELISA were compared. Eighty sera from patients with dengue virus infections, 24 sera from patients with Japanese encephalitis (JE), and 78 sera from patients with nonflavivirus infections, such as malaria, typhoid, leptospirosis, and scrub typhus, were used. The MRL test showed superior sensitivity for dengue virus infections (94 versus 89%), while the PanBio test showed superior specificity for JE (79 versus 25%) and other infections (100 versus 91%). The PanBio ELISA showed better overall performance, as assessed by the sum of sensitivity and specificity (F value). When dengue virus and nonflavivirus infections were compared, F values of 189 and 185 were obtained for the PanBio and MRL tests, respectively, while when dengue virus infections and JE were compared, F values of 168 and 119 were obtained. The results obtained with individual sera in the PanBio and MRL IgM ELISAs showed good correlation, but this analysis revealed that the cutoff value of the MRL test was set well below that of the PanBio test. Comparing the sensitivity and specificity of the tests at different cutoff values (receiver-operator analysis) revealed that the MRL and PanBio IgM ELISAs performed similarly in distinguishing dengue virus from nonflavivirus infections, although the PanBio IgM ELISA showed significantly better distinction between dengue virus infections and JE. The implications of these findings for the laboratory diagnosis of dengue are discussed.